Outage performance users located outside D2D coverage area in downlink cellular network - Thanh-Luan Nguyen; Dinh-Thuan Do (Bulletin of Electrical Engineering and Informatics, 2021)
Device-to-device (D2D) communication has been proposed to employ the proximity between two devices to enhance the overall spectrum utilization of a crowded cellular network. With the help of geometric probability tools, this framework considers the performance of cellular users under spatial separation with the D2D pair is investigated. The measurement results and analytical expression of outage probability show that the proposed frameworks improve the outage performance at a high signal-tonoise ratio (SNR) at the base station. Results also interpret that the distances between nodes in the D2D-assisted network make slight impacts on the performance of the cellular user.